Renewable energy systems - Themelis, Nickolas J.; Bronicki, Lucien Y.; Soder, Lennart; Vega, Luis A.; Kaltschmitt, Martin (Springer New York, 2013)
Humanity is facing a steadily diminishing supply of fossil fuels, causing researchers, policy makers, and the population as a whole to turn increasingly to alternative and especially renewable sources of energy to make up this deficit.  Gathering over 80 peer-reviewed entries from the Encyclopedia of Sustainability Science and Technologies, Renewable Energy Systems provides an authoritative introduction to a wide variety of renewable energy sources.  State-of-the-art coverage includes geothermal power stations, ocean energy, renewable energy from biomass, waste to energy, and wind power.  This comprehensive, two-volume work provides an excellent introduction for those entering these fields, as well as new insights for advanced researchers, industry experts, and decision makers.